TÜRKIYE BETWEEN PAST AND FUTURE: HISTORICAL ANALYSIS OF THE TRANSITION OF GOVERNMENT SYSTEMS - Safni, Pela; Hidayat, Ajat; Aziz, Ahmad; Erman, Erman; Hasnah, Radhiatul (Hukum tata Negara/Siyasah, 2025)
This research examines Türkiye, between the past and the present. Muslims experienced their second peak of glory when three great empires came to power, namely the Ottoman, Safavid, and Mughal (India) empires. The emergence of Islam in world history holds a number of unique things and wonders. However, after reaching its peak point during the time of Sultan Sulaiman Al Qanuni (1520-1566 M), the Ottoman Empire began to experience decline, weakened, and retreated towards its nadir until it met its moment of destruction. Throughout history, Türkiye was the first Islamic country to embrace a secular concept. The collapse of Ottoman Turkey and the development of modernization finally made Turkey maneuver into a secular state under the control of Mustafa Kemal Atatürk. He believes that only with a secular concept can Turkey rise and become a developed country like the West. However, these secularization efforts appear more as a form of coercion from the regime government, rather than secularization which is developing as a consequence of the modernization process as is happening in European countries. Therefore, genealogically, this article examines Turkey's conditions between the past and the present. The research method used is a historical research method that goes through four stages which include; heuristics (data collection), source criticism (examination of sources), interpretation (interpreting and analyzing sources), and historiography (writing history). This research is included in qualitative descriptive research using data from various secondary sources obtained from books, articles, and magazines which are of course relevant to this research. Türkiye; Now ; Past; Government System. Keyword: Türkiye; Now ; Past; Government System.